PELAKSANAAN PENYIDIKAN OLEH PENYIDIK PEGAWAI NEGERI SIPIL TERHADAP TINDAK PIDANA SEDIAAN FARMASI TANPA IZIN EDAR DI BPOM PADANG - Nurlinda Yenti, Neridesma (Normative Jurnal Ilmiah Hukum, 2018)
Civil Servant Investigators (PPNS) in carrying out their duties are under the coordination and supervision of police investigators. Given the authority to carry out the task of investigating the PPNS, it will certainly facilitate the disclosure of a specific criminal offense. The formulation of the problem was how the Investigation Process was carried out by Civil Servants Investigators Against the Criminal Procedure of Pharmaceutical Preparations without Circular Permits (Case Study at Padang's POM Center). Is the obstacle in carrying out the investigation by PPNS against criminal acts of pharmaceutical preparations without circulation permits at Padang's Center for Drug and Food Control?. The research method used is an approach that is carried out in a sociological juridical manner that is descriptive. This research data includes primary data and secondary data. Implementation of Investigation by Criminal Civil Servant Investigators against Unauthorized acts of pharmaceutical preparations in accordance with applicable laws and regulations, namely the Criminal Procedure Code. In carrying out investigations of PPNS BBPOM in Padang is under the coordination and supervision of police investigators. The constraints are the lack of budget funds and the number of BBPOM PPNS personnel in Padang that are not balanced with the area of ​​work. How to overcome obstacles is to propose additional budgets and set work strategies.